Cardiac autonomic responses to standing up and cognitive task in overtrained athletes - Hynynen, E.; Uusitalo, A.; Konttinen, N.; Rusko, H. (International Journal of Sports Medicine, 2008)
This study compared the autonomic responses to an active orthostatic test and Stroop Color Word Test (Stroop) as well as cognitive performance in Stroop in twelve severely overtrained (OA, 6 men and 6 women) and twelve control athletes (CA, 6 men and 6 women). RR-intervals were recorded during the orthostatic test, the Stroop, and a relaxation period succeeding the Stroop. Low frequency power during standing in the orthostatic test was lower in OA than in CA (1322 ± 955 ms2 vs. 2262 ± 1029 ms2, p = 0.030, respectively). During Stroop, OA had higher relative total power (50 ± 47 % vs. 19 ± 14 % of the individual total power during supine rest after awakening, p = 0.028, respectively) and high frequency power (38.5 ± 9.4 % vs. 13.5 ± 2.3 % of the individual high frequency power during supine rest after awakening, p = 0.035, respectively) than CA. In the Stroop, OA made more mistakes than CA (9.7 ± 6.5 % vs. 5.4 ± 3.0 %, p = 0.045). The increase in absolute total power from the Stroop to relaxation correlated negatively with the amount of mistakes in the Stroop (r = - 0.588, p = 0.003). Thus, cardiac autonomic modulation during orthostatic task and responses to cognitive task and to relaxation, as well as the cognitive performance were attenuated in severe overtraining.